Investigation into catalyst interactions in a dye-sensitized photoelectrochemical cell for water oxidation catalysis - Jewell, Carly Francis, author; Finke, Richard, advisor; Shores, Matthew, committee member; Krummel, Amber, committee member; Sampath, Walajabad, committee member (Colorado State University. Libraries, 2022)
Solar energy has the potential to contribute significantly to solving the global energy crisis. However, solar energy is both diffuse and intermittent, meaning the capture and storage of this energy is critical. One method of storing this energy is the generation of storable hydrogen fuel via photoelectrochemical water-splitting, that is, storing energy in chemical bonds, specifically the H-H bond. However, the efficiency of the water-splitting process is limited by the water oxidation reaction, a four-electron process occurring at the anode. As such, water splitting devices, and more specifically water-oxidation devices, have been the focus of research for several decades. One such strategy, employed herein, uses molecular light-harvesting dyes and associated materials to capture and convert energy from the sun into chemical bonds. The work presented in this dissertation examines one such water-oxidation dye-sensitized photoelectrochemical cell (DS-PEC) with the goal of better understanding how charge-carrier interactions in the system are impacted by varying the system's catalyst, architecture and device composition. Throughout this dissertation a photoanode consisting of nanostructured SnO2 coated in perylene diimide dye N,N'-bis(phosphonomethyl)-3,4,9,10-perylenediimide plus photoelectrochemically deposited cobalt oxide (CoOx) is examined. Chapter I provides an in-depth overview to water-oxidation catalysis with a focus on the state of DS-PECs in the literature. Chapter II looks to understand the impact of an alumina overlayer on this DS-PEC system, with the specific goal of better understanding why the addition of the CoOx catalyst decreases photocurrent and increases recombination, a so-called "anti-catalyst" effect. The studies presented in Chapter II demonstrate that the presence of an ultrathin alumina overlayer by atomic layer deposition (ALD) increases photocurrents and decreases recombination in the device, although the addition of CoOx catalyst still decreases photocurrent. Chapter III examines the same system with the continued goal of identifying the source of increased recombination and decreased photocurrents with CoOx catalyst addition. Through a series of controls, residual carbon attributable to organic stabilizer used in the nanostructured SnO2 synthesis is discovered to be the culprit of this "anti-catalysis" effect. Anodes made using more carbon-free SnO2 deposited by ALD, rather than the nanostructured SnO2 with residual carbon, show an increase in photocurrents with CoOx addition. Subsequently, Chapter IV looks at two methods of overcoming and outcompeting the recombination attributable to residual carbon in the device. The effect of the residual carbon is shown to be mitigated through both the use of a more active iridium-based catalyst, amorphous Li-IrOx, rather than CoOx, and then through the use of a more carbon-free ALD-SnO2, without organic stabilizer, rather than nanostructured SnO2. The planar ALD-SnO2 is compared to the nanostructured SnO2 both on a per dye basis and on an electrochemically active surface area basis. The results presented in this dissertation offer fundamental insights into achieving both a better understanding, and an improved performance, of DS-PECs for water-oxidation catalysis that is a critical component of solar energy capture and storage.
Keywords: dye-sensitized solar cell; perylene diimide; water oxidation; metal-oxide; catalysis; photoelectrochemical cell